Rekonstruksi Konsep Model Pendidikan Humanistik Telaah Atas Genosida Bangsa Palestina: Tinjauan Analisis Bibliometrik (2019-2023) - Huda, Ali Anhar Syi'bul; Hamdi, Hamdi; Nurhuda, Abid; Lathif, Nur Muhammad (ISLAMIC PEDAGOGY: Journal of Islamic Education, 2024)
This study discusses the reconstruction of the concept of a humanistic education model in the context of the Palestinian genocide. This conflict has had far-reaching impacts on humanistic education and development. The purpose of this study is to explore research trends related to humanistic education, analyze the contributions of productive researchers, and identify renewable issues based on a bibliometric review of 2019-2023 publications. This study uses bibliometric methods with data from 1,000 articles analyzed using the Publish or Perish and VOSViewer applications. The results showed a significant increase in the number of publications on humanistic education and Palestinian genocide, with a peak in 2022 (274 articles). Most publications are e-journals (970 articles), reflecting their global accessibility and relevance. Prolific researchers such as Ruslan Abdul Gani and Ahmad Zain Sarnoto made important contributions to this topic. Relevant new issues include freedom, human potential, and educational infrastructure. The conclusion of this study emphasizes the importance of humanistic education for trauma recovery, peace promotion, and strengthening cultural identity in Palestine specifically and generally in educational institutions in Indonesia. The limitation of this study lies in the limited use of databases. Recommendations for future research are to expand the use of international databases to enrich the analysis.